6x+1y=-31

Simple and best practice solution for 6x+1y=-31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+1y=-31 equation:


Simplifying
6x + 1y = -31

Solving
6x + 1y = -31

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1y' to each side of the equation.
6x + 1y + -1y = -31 + -1y

Combine like terms: 1y + -1y = 0
6x + 0 = -31 + -1y
6x = -31 + -1y

Divide each side by '6'.
x = -5.166666667 + -0.1666666667y

Simplifying
x = -5.166666667 + -0.1666666667y

You can always share this solution

See similar equations:

| 6n+10=8n-8 | | 52.5-24x+1.2x^2=0 | | (2x+10)+(2x+12)=90 | | 18+5x=3(10-x) | | x^3-3x^3=0 | | -8c+10=-8c-4 | | 1/3n-2/9 | | 2v-8=10-v | | 5x+2=-3+6x | | 4x+49+2x+11=90 | | 10-m=41 | | 20x-35=65 | | 5x=50-5x | | 3.4+(3.8+j)= | | 200x+315=50x-450 | | 4.4(-5+1.1h)= | | 13=3(x-1)-(x-8) | | 4x^2-17x+11=-4x+2 | | -8+6f=3f+10 | | 4x-3+x=52 | | -1.2(-1.3t)= | | 200=40x-90 | | 10-4r=-4r+10 | | 6(-5u+1)= | | 8x+50+(-5x)+34=90 | | ln(x)=(x^2)+1 | | -3+(v+4)= | | -1+3d=6+2d | | (3z)(-8)= | | 7/9k=5/15 | | -4(-6+7r)= | | w+-8=0 | | 2(12-k)-(k+2)=8(2-3k)-3(5-6k) | | 5x+650=5 | | 6+x=97 | | -5t+7t=h(t) | | 1+10g=-8+10g | | 6(-7+2d)= | | 15x-25=65 | | -1+(m+-4)= | | -9s=7-9s | | -5-6t=-6t-3 | | 3x+36=2x-45 | | -16t^2+940=h | | 20-305=65-40x | | -16t^2+1000=h | | 7+2z=3z | | 4/9=/63 | | -3(-4-2)=7 | | 200x+35=2-45 | | 160.00+0.85(1600)= | | -5j=-6-3j | | 4x+20=2x+66 | | 20=20x-90 | | 20=20x-9 | | -5b+b=-4b | | 9(2x+4)=18 | | -16t^2+1700=h | | 0.21(380)+41= | | -5(w+2)-w-3=-6(w+5)+17 | | 100x/5x | | 1-x/x | | 555-20x=5y | | 150x-5x=65 | | (1/4x)-8=4 |

Equations solver categories